Alcohol Consumption among Samoan Adults in 2010: Patterns, Correlates and Health Implications. (14th July 2020) - Jiang, Joy J; Reupena, Sefuiva M; Naseri, Take; Swift, Robert M; McGeary, John E; McGarvey, Stephen T
Abstract: Aims: We aim to describe alcohol consumption and related problems from a nationwide survey in 2010 in Samoa in association with sociodemographic variables as part of an intervention development. Methods: The sample consisted of 3463 adults, 25–65 years of age. Participants self-reported alcohol consumption in the previous 12 months, patterns of drinking and alcohol-related psychosocial problems. Data about age, census region of residence, highest attained education level, employment, marital status, household assets score and current smoking status were gathered. Results: More than one-third of men, 36.1%, and 4.1% of women consumed alcohol in the past year. There were greater proportions of alcohol users among younger adults, <45 years, in both men and women. Among men, being unemployed and residing outside of rural Savai'i and smoking cigarettes were associated with current alcohol use. Among women, tertiary education and cigarette smoking were strongly associated with alcohol use. Among alcohol consumers, almost 75% of both men and women reported being drunk more than once in the prior month, and 58% of men and 81% of women drank heavily, consuming >4 drinks for women and >5 drinks for men at least once per episode in the prior week. More men than women, 51% versus 26%, felt that alcohol consumption had interfered with their daily life. Conclusion: Our analyses identified correlates of alcohol consumption and associated problems that can help guide the development of targeted interventions for different sex and age groups to mitigate the social and physiological harms of alcohol misuse. Abstract : In our study sample of Samoan adults, 36% of men and 4% of women consumed alcohol, which was greater among younger adults, unemployed men, women with tertiary education and smokers. Heavy drinking was notable among all men and women consuming alcohol. These results indicate the importance of alcohol screening and intensive implementation research on suitable interventions.